Il Manzoni di Sapegno - Parisi, Luciano (Cuadernos de Filología Italiana, 2007)
Natalino Sapegno highlighted Manzoni’s solidarity with the downtrodden, his admiration for their culture, and his commitment to social justice. He defended Manzoni from the accusations of liberal and Marxist scholars, denying his so-called aristocraticism (and what others perceived as a condescending attitude), and showing how rich and intense the interior life of Manzoni’s humble main characters is. Finally, Sapegno understood that Manzoni’s rejection of violence was not an ideological ploy: it was a key component of the same spirituality from which the writer’s social commitment sprung.